PENERAPAN TEAM GAMES TOURNAMENTS (TGT) DALAM MENINGKATKAN AKTIFITAS BELAJAR DAN HASIL BELAJAR SANITASI HYGIENE - Lina - Mufidah; titik Sulistyani; Eka Rachmawati (Jurnal Socia Akademika, 2023)
This study aims to determine the increase in student learning activity and student learning outcomes. The method used is class action research (PTK) which consists of two cycles containing aspects of planning, implementation, evaluation and reflection. The instruments used are observation sheets of student learning activities and test sheets of learning outcomes. The subjects of this study are 52 students of the Culinary Arts Study Program for the 2022-2023 Academic Year. The results showed an increase in learning activity and student learning outcomes. The study's results found that applying the team's games tournaments (TGT) model can increase student activeness and learning outcomes, especially in theoretical courses. Sanitation hygiene learning using the quiz-assisted TGT learning model has carried out for two cycles in the first cycle; most respondents in the first cycle were still less active in education, as much as 27 (51.9%). While in cycle II, it was found that most of the learning activity in most categories was quite active, as much as 29 (55.8%). The learning outcomes of students can be concluded that there is an increase in learning outcomes in cycle I, most of which have learning outcomes above KKM as much as 34 (65.4%), while cycle II mostly has learning outcomes above KKM as much as 47 (90.4%).